The non-governmental organisation and financial institution: the Malaysian law perspective - Termizi, Mazbah; Mohd Jaafar, Noor Ismawati; Abdullah, Nurhidayah; Tagaranao, Mariam Saidona; Mohd Safian, Yasmin Hanani (2015)
The function of non-governmental organisation (NGO) could be beneficial to the societies especially when it involved the needy. To operate actively and meeting their establishment objectives, monetary supports from financial institutions is very much needed. The financial assistance given especially in forms of cash donations is commonly protected under the laws. The paper explored the roles played by the laws in order to motivate the financial institution (FI) to provide monetary support to NGO. In specific the paper focus on the Malaysian legislative point of view only which includes the definitions and its relevant acts. The findings would list the associated acts and reveals the term "societies" to be linked with NGO.